Inflammation 2001
DOI: 10.1007/978-94-015-9702-9_11
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Response in Mycobacterium Tuberculosis Infection

Abstract: Infection with Mycobacterium tuberculosis (MTB) is accompanied by an intense Jocal inflammatory response which may be critical to the pathogenesis of tuberculosis. Activation of components of the innate immune response, such as recruitment of polymorphonuclear (PMN) and mononuclear phagocytes and induction of pro-inflammatory cytokines, such as tumor necrosis factor a (TNF--a), by MTB occurs early after MTB infection, however, may persist as the organism establishes itselfwithin granulomas. MTB and its protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 71 publications
1
25
0
1
Order By: Relevance
“…IFN-gamma produced by all classes of lymphocytes and potentially by alveolar macrophages, up-regulates production of TNF-alpha [1,5,8]. In our study, we observed gradual decline of IFN-gamma serum levels during the first four weeks of treatment, especially in prednisone recipients.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…IFN-gamma produced by all classes of lymphocytes and potentially by alveolar macrophages, up-regulates production of TNF-alpha [1,5,8]. In our study, we observed gradual decline of IFN-gamma serum levels during the first four weeks of treatment, especially in prednisone recipients.…”
Section: Discussionsupporting
confidence: 51%
“…The interaction between T cells and macrophages is essential immune defense mechanisms in Mycobacterium tuberculosis (MTB) infection, resulting in the release production and release of pro-inflammatory cytokines such as tumor necrosis factor alpha (TNF-alpha) interferon gamma (IFN-gamma) and interleukin 1-beta (IL-1 beta) by these cells [1][2][3]. Cellular immune responses triggered by these inflammatory cytokines activate typical immune defense mechanisms against MTB inflammation [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Upregulated Smad3 mediates pro-fibrotic activities of TGF-b [71]. Therefore, TGF-b is involved as both a critical cytokine of immunosuppression and contributes to structural and cellular composition of lung granulomas [72]. Transcription of IDO in H37Rv-infected WT lungs was only modestly enhanced at d30 p.i., whereas gene transcription of tryptophanyl-tRNA synthetase (WARS) was strongly induced in iNOS -/-mice and modestly in WT mice.…”
Section: Immunosuppressionmentioning
confidence: 99%
“…The immune system sequesters persistent sources of antigen by establishment of a granulomatous barrier (36,47,53). Infections with Schistosoma mansoni or Mycobacterium spp.…”
mentioning
confidence: 99%